Desain Kolam Retensi Berbantu Komputer di Cibuluh Kota Bogor - Muhammad Nor Mahmudi; Setiawan, Budi Indra (Departemen Teknik Sipil dan Lingkungan IPB, 2020)
Water retention serves to control the surface runoff and conservation of rainwater in maintaining groundwater accumulation. This research aims to know the discharge of flood, know the volume of water to be accommodated in water retention, determine optimal water retention volume capacity, produce an effective design of water retention technical design, and produce a cost budget plan. Research conducted in Cibuluh Quarter, Tanah Baru Village, District Bogor Utara, Bogor City, West Java. Komulative flood discharge is 12.01 m3/sec. Capacity of Ciheuleut River is 9.38 m3/sec. Total capacity of water retention is 5272.52 m3. The Capacity development is 10481 m2. Water retention area that can be constructed is 4241 m2. The depth is 4 m so the capacity is 16964 m3. The structure is oval. The shortest diameter dimension is 50 m and the longest is 108 m. Total depth plan of 6 m is able to accommodate maximum 25446 m3 of water. Planned a type of sluice with width 1300 mm x height 1600 mm with a discharge of 4.89 m3/sec. It takes a total of 5 sluices on inlet and outlet. The cost required in the construction of Cibuluh Water Retention is Rp13.680.570.000,00.